Long-term corneal multifocal stability following a presbyLASIK technique analysed by a light propagation algorithm. - Villanueva, Asier; Vargas, Veronica; Mas, David; Torky, Magda; Alió, Jorge L (Clinical & Experimental Optometry, 2019)
Background: There is a lack of scientific evidence on long-term follow-up of the outcomes of the presbyLASIK techniques. This study aimed to objectively evaluate corneal stability three years following excimer laser central presbyLASIK.Methods: This is a longitudinal, retrospective, observation of a consecutive series of cases comprising 24 eyes which had been treated by central myopic or hyperopic Presbymax central presbyLASIK. Eyes treated with the same version of presbyLASIK software were included and followed by corneal topography at three months, one and three years after surgery. Based on the corneal topography data, customised software - based on a light propagation algorithm and developed using Matlab software - was used to analyse the simulated behaviour of light through the ocular media. The range of objective corneal depth of focus was also measured.Results: Results were assessed separately for myopes and hyperopes at pupillary diameters of 3.0 and 6.0 mm. The results showed corneal multifocality outcomes to remain constant (p > 0.05) throughout the three-year follow-up period.Conclusion: The use of light propagation analysis of the multifocal anterior corneal surface following a Presbymax central presbyLASIK procedure demonstrated stable outcomes over a three-year follow-up period.